Toxoplasma gondii genotypes and frequency in domestic cats from Romania - Adriana Györke; Anamaria Balea; Silvia Borșan; Chunlei Su; Tiantian Jiang; Cristian Magdaș; Daniel Mărcuțan; Radu Blaga; Viorica Mircean; Isabelle Villena; Furio Spano; Violeta Briciu; et al. (BMC Veterinary Research, 2024)
Abstract Background Toxoplasma gondii is a zoonotic protozoan parasite with a heteroxenus life cycle that involves felids as the definitive hosts and any warm-blooded animal, including humans, as intermediate hosts. Cats are key players in parasite transmission as they are capable of shedding high numbers of oocysts in their feces that contaminate the environment. Methods The study was performed on 31 domestic cats (31.23 ± 27.18 months old) originating from rural and urban areas (5.17:1) in the center and north-west Romania. Feces (n = 31), blood (n = 28), and heart samples (n = 27) were collected. Fecal samples were analyzed by flotation technique, and PCR (529 bp repetitive element). Fecal samples with T. gondii oocysts were bioassayed in mice. Serum samples were analyzed by modified agglutination test and ImmunoComb for the detection of specific anti-T. gondii IgG antibodies. Heart samples were bioassayed in mice, and analyzed by PCR. Toxoplasma gondii positive samples were genotyped by nPCR-RFLP targeting eleven genetic loci (SAG1, SAG2, alt-SAG2, SAG3, BTUB, GRA6, c22-8, c29-2, L358, PK1, and Apico). Results Toxoplasma gondii oocysts were found in 2 out of 31 fecal samples collected from a 3-months old stray kitten, and a 4-years old female. In total, 17 out of 27 sera were positive for T. gondii IgG antibodies. The antibody titers in MAT ranged from 1:6 to 1:384. Toxoplasma gondii DNA was detected in 7 out of 27 heart samples, and four of them were positive also by bioassay. Six T. gondii DNA samples from bioassayed mice could be assigned to ToxoDB PCR-RFLP genotype #1 or #3 (Type II) and one T. gondii DNA from heart digest to genotype #2 (Type III). Both of these genotypes are common in Europe. Conclusions Our results revealed that the infection with T. gondii is still high in cats from Romania. The oocysts shedded by these cats represent an important source of infection for intermediate hosts, including humans. Further studies on a wider range of cases are necessary for a more exhaustive definition of the T. gondii genotypes circulating in Romania.